Mobile pervasive augmented reality systems - MPARS: the role of user preferences in perceived quality of experience in outdoor applications - Pascoal, R.; de Almeida, A.; Sofia, R. C. (ACM Transactions on Internet Technology, 2020)
After briefly introducing aspects concerning Mobile Augmented Reality Systems, this article delves into the evolution of these systems as pervasive technology. The work debates also on acceptance of this technology in the context of outdoor applications. The need to develop context-aware, close-to-real-time feedback mechanisms that take into consideration a continuous measurement of Quality of Experience is also discussed. For this purpose, the work goes over how to integrate user preferences into context-aware feedback systems, proposing a theoretical model for measuring Quality of Experience. The model is derived from an analysis of previous technology adoption models and incorporates the knowledge of user preferences. This knowledge has been gathered via a public questionnaire.